Drum Composting: A Unique Solution in Environmental Engineering for Biodegradable Waste Management and Electricity Generation - Salve, Sachin; Shinde, Sunil; Bhojwani, Kunal (AMC Indian Journal of Civil Engineering, 2021)
In Civil Engineering or rather in Environmental engineering, waste management is a very tedious problem nowadays. This paper discusses the drum filling process as one of the best methods of biodegradable waste management technique, as it reduces tonnes of biodegradable waste from the environment and some innovative investigations are found to validate the potential of collecting electrical energy from biodegradable waste. The energy is accumulated by inserting a moisture sensor into a drum filled with compost to allow flow of ions to generate electricity. In addition, this research has the ability to light up small LED light which can be used for low power electrical consumption appliances like lamps, torch, etc. in the future.